A tension-independent mechanism reduces Aurora B-mediated phosphorylation upon microtubule capture by CENP-E at the kinetochore. Issue 12 (18th June 2019) - Taveras, Carmen; Liu, Chenshu; Mao, Yinghui
ABSTRACT: During mitosis, Aurora B kinase is required for forming proper bi-oriented kinetochore-microtubule attachments. Current models suggest that tension exerted between a pair of sister-kinetochores (inter-kinetochore stretch) produces a spatial separation of Aurora B kinase from kinetochore-associated microtubule binding substrates, such as the Knl1-Mis12-Ndc80 (KMN) network, resulting in a decrease of phosphorylation and, thus, an increase of affinity for microtubules. Using Single-Molecule High-Resolution Colocalization (SHREC) microscopy analysis of the kinetochore-associated motor CENP-E, we now show that CENP-E undergoes structural rearrangements prior to and after tension generation at the kinetochore, and displays a bi-modal Gaussian distribution on a pair of bi-oriented sister kinetochores. The conformational change of CENP-E depends on its microtubule-stimulated motor motility and the highly flexible coiled-coil between its motor and kinetochore-binding tail domains. Chemical inhibition of the motor motility or perturbations of the coiled-coil domain of CENP-E increases Aurora B-mediated Ndc80 phosphorylation in a tension-independent manner. Metaphase chromosome misalignment caused by CENP-E inhibition can be rescued by chemical inhibition of Aurora B kinase. Furthermore, a pair of monotelic sister-kinetochores shows asymmetric levels of Aurora B-mediated phosphorylation in mono-polar spindles depending on CENP-E motor activity. These results collectively suggest a tension-independent mechanism to reduce Aurora B-mediated phosphorylation of outer kinetochore components in response to microtubule capture by CENP-E.